Stress and Emotion Management as the Key to Success for MSME Owners: Case Study of Selogiri Village MSMEs - ash-shiddiqy, muhammad (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2023)
This research is motivated by the awareness of the importance of stress and emotion management in the success of small and medium-sized enterprises (SMEs). The aim of this study is to provide a better understanding of the significance of stress and emotion management for SME owners and to assist in implementing stress and emotion management techniques. The research conducted is qualitative research using the ABCD method. The subjects of this study are SME owners in Selogiri Village, Kebumen. Data collection techniques were carried out through interview observations. The results of this study indicate that stress management has a significant impact on SME practitioners in developing their products. Based on the data obtained, SME practitioners in Selogiri Village mentioned that stress arises from comments made by some consumers. Their approach to managing stress is to evaluate their products based on the comments given by consumers, so they believe that improving the quality of their products can silence consumers with negative comments. Stress management in this context means turning hate comments into product evaluation materials for SME practitioners.